Factors Influencing Households Willingness To Pay For Water In Penang And Perak - Chew, Kah Hooi (2014)
In carrying out water services industry reform plan, Suruhanjaya Perkhidmatan Air Negara (SPAN) recommended for consumers not to continue their dependency on the government to fund subsidy for water. However, increasing water tariff is politically sensitive issue. Hence, to determine a justifiable and affordable water rate, this study is carried out to examine factors that influence water users' willingness to pay for water. The study is using quantitative method to measure predictors for willingness to pay and perceived water value. Survey questionnaire had been conducted in one month duration in Penang and Perak, where Penang has the lowest water rate currently and Perak had not been revised the water rate for many years. Attribution theory is apply to observe how water users response towards the statements and situation given in the questionnaire.